Multi-source solid waste composite filling cementitious material, preparation method thereof and filling material containing the same

CN119241191BActive Publication Date: 2026-10-20CHANGCHUN GOLD RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411378494.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2026-10-20
Estimated Expiration
2044-09-30

Smart Images

  • Figure BDA0005069286540000101
    Figure BDA0005069286540000101
  • Figure BDA0005069286540000111
    Figure BDA0005069286540000111
  • Figure BDA0005069286540000131
    Figure BDA0005069286540000131
Patent Text Reader

Abstract

The application provides a multi-source solid waste composite filling cementing material, a preparation method thereof and a filling material containing the material, and belongs to the field of building materials. In the application, gypsum separated and extracted from biological oxidation liquid is modified by sodium sulfate, and various solid wastes such as gypsum, water slag and fly ash are mixed to effectively reduce the use cost of the cementing material. The multi-source solid waste composite filling cementing material provided by the application comprises the following raw materials in parts by weight: 15.5-20.5 parts of gypsum, 10-15 parts of sodium sulfate, 22.5-27.5 parts of water slag powder, 22.5-27.5 parts of fly ash, 2.5-7.5 parts of cement clinker, 7.5-12.5 parts of quicklime and 0.5-2 parts of active activator. The cementing material contains more active components, has fast hydration speed, more hydration products and short setting time, and the filling material prepared by using the cementing material has high strength indexes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of building materials, specifically to a multi-source solid waste composite filling cementitious material, its preparation method, and filling materials containing the material. Background Technology

[0002] Tailings are solid waste discharged from mines after grinding ores to extract valuable elements. Using tailings as aggregate and cementing material for backfilling mined-out areas is an important way for mines to dispose of large quantities of solid waste. However, with the continuous improvement of mineral processing recovery rates, the particle size of tailings produced by processing plants is becoming increasingly fine. The fine particle size and poor permeability of tailings themselves lead to long-standing problems in mine backfilling, such as difficulty in slurry settling and concentration, low dewatering efficiency in the stope, and slow strength development of the backfill.

[0003] On the other hand, with rising cement prices, the cost of backfill cementitious materials remains high. Using solid waste to replace industrial raw materials in the preparation of backfill gel materials is one of the key areas of focus for technical personnel. This approach not only achieves the resource utilization of waste but also reduces the preparation and use costs of backfill cementitious materials, which is of great significance for promoting the construction of green mines. However, how to adjust the raw material ratio and preparation method of backfill cementitious materials to improve their filling performance requires further research and solutions.

[0004] In view of this, it is necessary to design a multi-source solid waste composite filling cementitious material, its preparation method, and filling material containing the material to solve the above problems. Summary of the Invention

[0005] In view of the technical problems existing in the background art, this application utilizes sodium sulfate to modify gypsum separated and extracted from biological oxidation liquid, rationally designs the raw material composition and ratio, and mixes various solid wastes such as gypsum, water slag, and fly ash to provide a multi-source solid waste composite backfill cementitious material, its preparation method, and backfill material containing the material. It aims to solve the problems of difficult slurry sedimentation and concentration, low dewatering efficiency in mining backfill, slow strength development of backfill body, and excessively high cost of backfill cementitious materials.

[0006] In a first aspect, embodiments of this application provide a method for preparing a multi-source solid waste composite backfill cementitious material, comprising the following steps:

[0007] S1. Mix water slag and water at a mass ratio of (0.8-1.2):1 to form a slurry, pour it into a ball mill for mechanical activation, dry it in an oven, grind it, and sieve it to obtain water slag powder.

[0008] S2, prepare a sodium sulfate solution with a concentration of 30%-80%, and spray the sodium sulfate solution evenly onto the gypsum surface without dead angles according to the expected weight parts through a spraying device. After drying in an oven, grind to obtain gypsum powder with a fineness greater than 200 mesh.

[0009] S3, Sodium hydroxide and water glass in a mass ratio of (0-3):4 are mixed evenly to obtain an active activator;

[0010] S4. The gypsum powder, the water slag powder, the active activator, fly ash, cement clinker and quicklime are mixed and stirred evenly according to the expected weight parts to obtain the multi-source solid waste composite filling cementitious material.

[0011] In some embodiments, in step S1, the mechanical activation time is 30-50 minutes, the sieving is performed by vibrating sieving of the water slag through a 200-mesh sieve, and the drying oven is set to 100-105℃ for 24-28 hours; the activity coefficient of the water slag powder is ≥0.25, and the specific surface area is ≥600 m². 2 / kg.

[0012] In some embodiments, in step S3, the water glass is industrial powder sodium silicate with an effective content greater than 95% and a modulus of 1.5; the sodium hydroxide is industrial powder sodium hydroxide with an effective content greater than 90%.

[0013] In some embodiments, in step S2, the oven is set to 100-105℃ for 12-16 hours, and the sodium sulfate solution is prepared using industrial powdered sodium sulfate with an effective content greater than 90%.

[0014] In some embodiments, in step S4, the cement clinker is silicate cement clinker, wherein the total mass percentage of CaO, SiO2, Al2O3 and Fe2O3 in the silicate cement clinker is greater than 95%; and the quicklime is calcareous quicklime with a CaO mass percentage of more than 60%.

[0015] Secondly, embodiments of this application provide a multi-source solid waste composite backfill cementitious material, which is prepared according to any of the aforementioned schemes. The multi-source solid waste composite backfill cementitious material comprises the following raw materials in parts by weight: 15.5-20.5 parts gypsum powder, 10-15 parts sodium sulfate, 22.5-27.5 parts water slag powder, 22.5-27.5 parts fly ash, 2.5-7.5 parts cement clinker, 7.5-12.5 parts quicklime, and 0.5-2 parts activity activator. The gypsum powder is prepared from gypsum extracted and separated from a biological oxidation liquid.

[0016] In some embodiments, the initial setting time of the slurry of the multi-source solid waste composite filling cementitious material is 40-50 min, and the final setting time is 380-400 min.

[0017] Thirdly, embodiments of this application provide a filling material, including the multi-source solid waste composite filling cementitious material and tailings in the aforementioned scheme.

[0018] In some embodiments, the tailings include ultrafine gold mine tailings or tailings with a fineness of 100-400 mesh.

[0019] In some embodiments, the filler has a spread of 20-50 cm and a later strength of 2.3-2.5 MPa.

[0020] The beneficial effects of this application are:

[0021] (1) This application uses gypsum extracted from bio-oxidation liquid as a base material, and also utilizes other industrial solid wastes such as slag and fly ash. This not only reduces the consumption of non-renewable resources such as cement, but also improves the utilization rate of waste resources. It solves the problem of stockpiling and disposal of gypsum, a by-product generated during the bio-oxidation liquid treatment process, and conforms to the concept of green and waste-free production. Since the cost of this gypsum is much lower than that of similar cement, the cost of filling gel materials is further reduced, creating new economic benefits for enterprises.

[0022] (2) The preparation method of the multi-source solid waste composite filling cementitious material provided in this application uses sodium sulfate to modify the gypsum separated and extracted from the biological oxidation liquid, and rationally designs the raw material composition and ratio, which effectively improves the water retention performance of the cementitious material and greatly improves the later strength of the cementitious material and the filling material. The preparation method provided in this application is simple and efficient and is convenient for industrial production.

[0023] (3) The multi-source solid waste composite backfill cementitious material provided in this application can be used for backfilling ultrafine tailings in gold mines. It can directly replace the mainstream cement products currently used for mine backfilling, and has a finer particle size, more active ingredients, and faster hydration speed. It can effectively solve the problems of slow setting time and low early strength of ultrafine tailings backfill. When applied to backfilling other tailings with coarser gradations, it can appropriately reduce the mechanical activation time of water slag in the multi-source solid waste composite backfill cementitious material.

[0024] (4) The multi-source solid waste composite filling cementitious material prepared in this application has a shorter setting time than P.O42.5 ordinary silicate cement paste, and the expansion of the filling material prepared by this cementitious material is 20-50cm, and the later strength is 2.3-2.5MPa, which are all better than the filling material prepared by P.O42.5 ordinary silicate cement paste.

[0025] The short setting time and high strength of the multi-source solid waste composite backfill cementitious material are due to the presence of two reaction systems during its setting process. Firstly, gypsum powder and mechanically activated slag powder form a sulfate reaction system, in which gypsum provides some SO4 for the formation of hydration products. 2- In addition to a suitable alkaline environment, another part of the reaction requires SO4. 2- Provided by sodium sulfate, in the reaction, gypsum and sodium sulfate simultaneously activate the slag to generate calcium sulfoaluminate and ettringite crystals. This method effectively improves the water retention performance of cementitious materials and promotes the early and mid-term strength enhancement of filling materials and the generation of early and mid-term hydration products. Secondly, this application also introduces fly ash, quicklime, cement clinker and active activator to form an alkaline reaction system, which accelerates the hydration rate of materials and increases the amount of hydration products in the later stage, generating hydrated calcium aluminosilicate gel, hydrated calcium silicate and other hydration products. The ettringite generated in the early stage of setting and the hydrated calcium aluminosilicate gel generated in the later stage continuously crystallize, promoting the continuous progress of the reaction. At the same time, through the close interweaving of the two in the material, the setting strength of the material in the later stage is greatly improved.

[0026] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Detailed Implementation

[0027] The embodiments of the technical solution of this application will be described in detail below. The following embodiments are only used to illustrate the technical solution of this application more clearly, and are therefore only examples, and should not be used to limit the scope of protection of this application.

[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification and claims of this application are intended to cover non-exclusive inclusion.

[0029] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.

[0030] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0031] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.

[0032] In recent years, due to rising cement prices and insufficient tailings dam capacity, the cost of backfilling and cementing for mining enterprises has remained high. At the same time, with the continuous improvement of mineral processing recovery rates, tailings particles are becoming increasingly fine. The fine particle size and poor permeability of tailings have led to problems in mine backfilling, such as difficulty in slurry settling and concentration, low dewatering efficiency in the stope, and slow strength growth of the backfill.

[0033] This application utilizes sodium sulfate to modify gypsum extracted from biological oxidation liquid, rationally designs the raw material composition and ratio, and mixes various solid wastes such as gypsum, water slag, and fly ash to provide a multi-source solid waste composite filling cementitious material, its preparation method, and filling material containing the material. This effectively improves the water retention performance of the cementitious material, significantly increases the later strength of the cementitious material and filling material, and reduces the use cost of the cementitious material.

[0034] In a first aspect, this application provides a method for preparing a multi-source solid waste composite filling cementitious material, comprising the following steps:

[0035] S1. Mix water slag and water at a mass ratio of (0.8-1.2):1 to form a slurry, pour it into a ball mill for mechanical activation, dry it in an oven, grind it in a ball mill, and sieve it to obtain water slag powder.

[0036] S2, prepare a sodium sulfate solution with a concentration of 30%-80%, and spray the sodium sulfate solution evenly onto the gypsum surface without dead angles according to the expected weight parts through a spraying device, dry it in an oven, and finally grind it to a fineness greater than 200 mesh to obtain gypsum powder;

[0037] S3, Sodium hydroxide and water glass are mixed evenly in a mass ratio of (0-3):4 to obtain an active activator;

[0038] S4. Gypsum powder, water slag powder, active activator, fly ash, cement clinker and quicklime are mixed and stirred evenly according to the expected weight parts to obtain the multi-source solid waste composite filling cementitious material.

[0039] Further, in step S1, the mechanical activation time is 30-50 minutes, the sieving is performed by vibrating sieving of the water slag through a 200-mesh sieve, and the drying oven is set to 100-105℃ for 24-28 hours; the activity coefficient of the water slag powder is ≥0.25, and the specific surface area is ≥600m². 2 / kg, meeting the requirements for water slag used in cement production in national standards.

[0040] Furthermore, in step S2, the oven is set to 100-105℃ for 12-16 hours. The sodium sulfate solution is prepared using industrial powder sodium sulfate with an effective content of more than 90%. The concentration of the sodium sulfate solution should not be less than 30%, otherwise too much water will be sprayed onto the gypsum, which will lead to a longer drying time for the gypsum.

[0041] Furthermore, in step S3, the water glass is industrial powder sodium silicate with an effective content greater than 95% and a modulus of 1.5; the sodium hydroxide is industrial powder sodium hydroxide with an effective content greater than 90%.

[0042] Further, in step S4, the cement clinker is silicate cement clinker, and the total mass percentage of CaO, SiO2, Al2O3 and Fe2O3 in the silicate cement clinker is greater than 95%; the quicklime is calcareous quicklime with a CaO mass percentage of more than 60%; and the mixing time is 400-600s.

[0043] Secondly, this application provides a multi-source solid waste composite filling cementitious material, which is prepared by the preparation method described in any of the aforementioned technical solutions, comprising the following raw materials in parts by weight: 15.5-20.5 parts gypsum powder, 10-15 parts sodium sulfate, 22.5-27.5 parts water slag powder, 22.5-27.5 parts fly ash, 2.5-7.5 parts cement clinker, 7.5-12.5 parts quicklime, and 0.5-2 parts activity activator.

[0044] The gypsum powder is prepared from gypsum extracted from biological oxidation liquid.

[0045] The production area for separating and extracting gypsum from biological oxidation liquid is generally not far from the production areas for solid wastes such as slag powder and fly ash. The material transportation and procurement costs are relatively low, which is conducive to industrial production and large-scale application.

[0046] Furthermore, in some embodiments, the initial setting time of the slurry of the multi-source solid waste composite filling cementitious material is 40-50 min, and the final setting time is 380-400 min.

[0047] The multi-source solid waste composite filling cementitious material provided in this application has two reaction systems during the coagulation process: one is a sulfate reaction system, which mainly exists in the early and middle stages of coagulation; the other is an alkaline reaction system, which mainly exists in the later stages of coagulation.

[0048] (1) Sulfate reaction system: The main raw materials participating in the reaction in this system are gypsum powder, water slag powder and sodium sulfate. Among them, gypsum provides some SO4 for the formation of hydration products. 2- In addition to a suitable alkaline environment, another part of the reaction requires SO4. 2- Provided by sodium sulfate. In the reaction, gypsum and sodium sulfate simultaneously activate the slag to generate calcium sulfoaluminate and ettringite crystals. These two products can enhance the strength of the material in the early and middle stages of setting. In addition, the ettringite crystals contain a large number of water molecules, which effectively improves the workability of the material.

[0049] While the aforementioned reaction system can enhance the strength of the material in the early and middle stages of solidification, it still presents several problems. First, the structure of ettringite, the main product of the aforementioned reaction system, is unstable and cannot guarantee the strength of the material in the later stages. Second, a certain amount of calcium sulfite, a byproduct, is generated during the reaction, which can easily hinder the solidification of the material. Third, the low Al and Si content in the slag powder is unfavorable for the formation of a large number of hydration products in the later stages. Therefore, a second reaction system is needed to further enhance the final solidification strength of the material.

[0050] (2) Alkaline Reaction System: The main raw materials involved in this system are fly ash, cement clinker, quicklime, water glass, and sodium hydroxide. Fly ash contains a relatively high amount of SiO2 and Al2O3, which can provide Al and Si for the formation of subsequent hydration products. In the reaction, firstly, the strong alkali sodium hydroxide dissolves and destroys the vitreous structure of the fly ash to activate its activity. Quicklime provides the Ca required for the reaction. 2+ and OH - The process involves raising the water temperature to accelerate the hydration reaction. Then, the cement clinker induces the hydration reaction, and under the stimulation of water glass, hydrated calcium aluminosilicate gel, hydrated calcium silicate, and other hydration products are generated, with hydrated calcium aluminosilicate gel being the main product. Finally, the ettringite generated during the early setting process and the hydrated calcium aluminosilicate gel generated later continuously crystallize, promoting the continuous progress of the reaction. At the same time, the close interweaving of the two in the material enhances the later setting strength of the material.

[0051] Thirdly, this application provides a filling material, which includes the multi-source solid waste composite filling cementitious material and tailings in the aforementioned scheme, wherein the tailings include gold mine tailings or other tailings with a fineness of 100-400 mesh.

[0052] Furthermore, in some embodiments, the expansion of the filling material is 20-50 cm, and the later strength is 2.3-2.5 MPa. This filling material is used for filling in mining, and its strength index at the same age exceeds the strength of the filling material prepared by P.O42.5 ordinary Portland cement by more than 20%.

[0053] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0054] The raw materials used in the embodiments provided in this application are described as follows:

[0055] (1) Gypsum: It is an industrial by-product extracted from biological oxidation liquid. It has a water content of about 15%, a pH value of 11-12, and few toxic and harmful components. Its main chemical components are shown in Table 1.

[0056] Table 1. Main components (wt%) of gypsum extracted from bio-oxidation solution

[0057] content(%) 3.39 10.34 34.44 8.4 0.16 31.9 white As Cr Pb Cd other - content(%) 0.0015 0.0013 0.0062 0.00074 11.36 -

[0058] (2) The activity coefficient of the water slag is ≥0.25, which meets the requirements of the national standard for water slag used in cement production. Its main chemical composition is shown in Table 2.

[0059] Table 2. Main components of water slag (wt%)

[0060] content(%) 21.31 11.26 46.13 6.31 0.49 2.58 0.24

[0061] (3) Fly ash: Class I general solid waste, which can be used for underground backfilling. Its main chemical components are shown in Table 3.

[0062] Table 3. Main components of fly ash (wt%)

[0063] content(%) 53.29 17.00 4.38 1.10 2.88 1.45 5.20 0.62

[0064] (4) Sodium sulfate: Industrial powder sodium sulfate with an effective content of more than 90%.

[0065] (5) Quicklime: Calcium quicklime with a CaO content of more than 60%.

[0066] (6) Cement clinker: Silicate cement clinker with a total content of CaO, SiO2, Al2O3 and Fe2O3 greater than 95%.

[0067] (7) Water glass: industrial powder sodium silicate with an effective content of more than 95% and a modulus of 1.5.

[0068] (8) Sodium hydroxide: Industrial powder sodium hydroxide with an effective content of more than 90%.

[0069] It should be noted that there may be differences in composition between gypsum products extracted from different biological oxidation solutions, and between gypsum products extracted from different biological oxidation solutions and commercially available gypsum products. Similarly, there are also such differences between water slag and fly ash, which are both solid wastes, and commercially available products. This situation is unavoidable. Therefore, in specific implementation, the formulation composition of this application should be appropriately adjusted according to the composition of the solid waste. Those skilled in the art should understand that such adjustments, within a reasonable range, will not affect the practicality of this application.

[0070] I. Preparation Method

[0071] Example 1

[0072] This embodiment provides a multi-source solid waste composite filling cementitious material, comprising the following raw materials in parts by weight: 18 kg gypsum powder, 13 kg sodium sulfate, 26 kg water slag powder, 26 kg fly ash, 6 kg cement clinker, 10 kg quicklime, and 1 kg activation activator.

[0073] This embodiment also provides a method for preparing a multi-source solid waste composite filling cementitious material, the specific steps of which are as follows:

[0074] S1. Water slag and water are mixed at a mass ratio of 0.8:1 and poured into a ball mill for mechanical activation for 40 minutes. The activated slurry is then placed in a drying oven at 105℃ for 24 hours to dry the slag to a constant weight. The slag is then ground to obtain slag micro-powder. During the grinding process, the slag micro-powder is sieved through a 200-mesh vibrating sieve, and a laser particle size analyzer is used to detect the particle size of the slag micro-powder samples to check if the surface area of ​​the slag micro-powder exceeds 600 m². 2 / kg, to ensure thorough grinding.

[0075] S2, sodium sulfate is prepared into a 30% concentration liquid and sprayed evenly onto the gypsum extracted by biological oxidation liquid. Then the gypsum is placed in an oven at 105℃ for 12 hours to dry to constant weight, and then ground to obtain gypsum powder with a fineness greater than 200 mesh.

[0076] S3, sodium hydroxide and water glass are mixed evenly in a mass ratio of 1:4 to obtain an active activator.

[0077] S4. The water slag powder, gypsum powder, active activator, sodium sulfate, fly ash, cement clinker and quicklime prepared in steps S1-S3 are poured into a high-speed mixer and stirred for 500s to make them evenly mixed, so as to obtain a multi-source solid waste composite filling cementitious material.

[0078] Examples 2-3 and Comparative Examples 1-8

[0079] The differences between Examples 2-3 and Comparative Examples 1-8 and Example 1 are as follows: Examples 2-3 changed the raw material ratio of the multi-source solid waste composite backfill cementitious material and the mechanical activation time of the water slag; Comparative Examples 1-8 changed the raw material ratio of the multi-source solid waste composite backfill cementitious material. Other aspects are largely the same as in Example 1 and will not be repeated here. The mechanical activation times of the water slag in Examples 2-3 were 30 min and 50 min, respectively. The raw material compositions of Examples 1-3 and Comparative Examples 1-8 are shown in Table 4.

[0080] Table 4. Raw material composition of Examples 1-3 and Comparative Examples 1-8

[0081]

[0082] Comparative Examples 9-10

[0083] The difference between Comparative Examples 9-10 and Example 1 is that the mechanical activation time of the water slag was changed; otherwise, they are largely the same as Example 1 and will not be repeated here. The mechanical activation time and specific surface area of ​​the water slag powder in Examples 1-3 and Comparative Examples 9-10 are shown in Table 5.

[0084] Table 5. Mechanical activation time and specific surface area of ​​slag powder in Examples 1-3 and Comparative Examples 9-10

[0085] Example 1 40 687 Example 2 3z 642 Example 3 50 673 Comparative Example 9 20 589 Comparative Example 10 60 691

[0086] Please refer to Table 5. As can be seen, a mechanical activation time of less than 30 minutes results in an excessively small specific surface area of ​​the slag powder, which is detrimental to subsequent mixing and penetration with gold ore tailings. While a mechanical activation time of more than 50 minutes can make grinding more thorough, the potential for improvement is limited, and it also increases the preparation cost. Therefore, the optimal mechanical activation time is 30-50 minutes.

[0087] Examples 4-6 and Comparative Examples 11-20

[0088] Examples 4-6 and Comparative Examples 11-20 each provide a filling material, which is prepared by the following method: the multi-source solid waste composite filling cementitious material prepared in Examples 1-3 and Comparative Examples 11-20 is mixed with gold mine tailings at a ash-to-sand ratio of 1:4, and then water is added to prepare a slurry with a mass concentration of 65%, thus obtaining the corresponding filling material, as shown in Table 6.

[0089] Table 6. Sources of multi-source solid waste composite filling gel materials used in Examples 4-6

[0090]

[0091] Comparative Example 21

[0092] The difference between Comparative Example 21 and Examples 4-6 and Comparative Examples 11-20 is that P.O42.5 ordinary silicate cement paste was used to prepare the filling material. Specifically, P.O42.5 ordinary silicate cement paste was mixed with gold mine tailings at a ash-to-sand ratio of 1:4, and then water was added to prepare a slurry with a mass concentration of 65%, which yielded the corresponding filling material.

[0093] II. Testing Methods

[0094] (1) Particle size detection and analysis

[0095] The slag powder was sieved through a 200-mesh vibrating screen to prevent insufficient grinding. Then, samples of the sieved slag powder were taken using a fractionation method and analyzed using a laser particle size analyzer to check if the surface area of ​​the slag powder exceeded 600 m². 2 / kg.

[0096] (2) Condensation time test

[0097] The cementitious material to be tested was prepared into mortar with a water-to-solid ratio of 0.5 and poured into a circular mold. The mold was then stored in a dark, sealed environment at approximately 20°C. The initial setting time was measured every 5 minutes using a Vicat apparatus, and the final setting time was measured every 30 minutes after the initial setting.

[0098] (3) Flow property test of filling material

[0099] Fill the mold with filling material and place it upside down on the vibrating table. Lift the mold and turn on the vibrating table to allow the slurry to diffuse freely. Once the slurry stops diffusing, turn off the vibrating table and measure the diffusion diameter three times with a ruler. Take the average value.

[0100] (4) Strength test of filling material

[0101] The filling material was placed into a triplet mold measuring 70.7×70.7×70.7mm and cured in a standard concrete curing chamber with constant temperature and humidity at 20±1℃ and 95% humidity. The compressive strength of the filling material was tested using an AEC-01 cement strength testing machine after 3d, 7d, and 28d of curing. These values ​​correspond to the early, mid-term, and late-term strengths of the filling material, respectively.

[0102] III. Analysis of Test Results for Each Embodiment and Comparative Example

[0103] The setting time of the multi-source solid waste composite filling cementitious materials prepared in Examples 1-3 and Comparative Examples 1-10 was tested according to the method in test method (2), and the test results were compared with the setting time of P.O42.5 ordinary silicate cement paste. The test results are shown in Table 7.

[0104] Table 7. Setting times of cementitious materials and P.O42.5 ordinary Portland cement paste prepared in Examples 1-3 and Comparative Examples 1-10

[0105]

[0106] The fluidity and strength of the fillers prepared in Examples 4-6 and Comparative Examples 11-20 were tested according to the test methods (3) and (4), and the test results were compared with the fluidity and strength of P.O42.5 ordinary silicate cement paste. The test results are shown in Table 8.

[0107] Table 8. Flowability and strength of the fillers prepared in Examples 4-6 and Comparative Examples 11-20

[0108]

[0109]

[0110] Please refer to Table 7. It can be seen that the initial setting time of the mortar prepared with the cementitious materials prepared in Examples 1-3 is 72-87 min, and the final setting time is 264-301 min, both of which are shorter than the initial setting time and final setting time of P.O42.5 ordinary Portland cement paste.

[0111] Please refer to Table 8. First, it can be seen that the diffusion range of the filling material prepared in Examples 4-6 is 21.5-27.6 cm, which is greater than that of the filling material prepared by P.O42.5 ordinary silicate cement paste. This indicates that the multi-source solid waste composite filling cementitious material provided in this application can bind more water molecules during the hydration process and has good water retention performance.

[0112] Secondly, it can be seen that, due to the finer particle size and higher active ingredient content of the multi-source solid waste composite backfill cementitious material provided in this application, the backfill material prepared by mixing this cementitious material with fine-grained gold mine tailings exhibits a higher strength growth rate and better performance indicators than the backfill material prepared by P.O42.5 ordinary Portland cement during the backfilling process. In terms of performance indicators, the early strength, mid-term strength, and late-term strength of the backfill material prepared by this cementitious material are all more than 20% higher than the strength of the backfill material prepared by P.O42.5 ordinary Portland cement at the same age.

[0113] Furthermore, it can be seen that the mechanical activation time of the slag further affects the strength performance of the filler material prepared using it by influencing the surface area of ​​the slag powder. This is because when the mechanical activation time of the slag is less than 30 minutes, although the setting time of the mortar is not significantly different from that in Example 1, when it is prepared as filler material for backfilling, less cementitious material can penetrate between the fine particles of gold mine tailings, resulting in a certain degree of decline in the backfilling effect. In this example, gold mine tailings with a fineness grade are used, which requires a high degree of fineness of the slag. When applied to backfilling other tailings with coarser gradations, the mechanical activation time can be appropriately reduced.

[0114] Referring to Tables 7 and 8, it can be seen that, compared with Example 1, reducing the relative content of fly ash, quicklime, and cement clinker in the raw materials of Example 3 can shorten the setting time of the cementitious material. However, the early strength of the filler prepared using it (Example 6) is not high because there is a lack of sufficient sulfate ions to generate ettringite to improve early strength. However, with the generation of a large amount of hydrated calcium aluminosilicate gel and other hydration products in the later stage, the later strength is improved. Compared with Example 1, increasing the relative content of fly ash, quicklime, and cement clinker in Example 2 will make the setting time of the cementitious material longer. In addition, the early strength of the filler prepared using it (Example 5) increases faster. As more and more ettringite and calcium sulfoaluminate are generated, the hydration and hardening speed of the cement increases faster and faster, which also greatly increases the mid-term strength. However, since the structure of ettringite is not stable, it does not contribute much to the growth of the later strength of the material, so the later strength is not high.

[0115] Based on the foregoing and the test results of Comparative Examples 1-4 and 11-14, it can be seen that the mass percentage of gypsum should be controlled below 25%. The total amount of fly ash, quicklime, and cement clinker should decrease as the amount of gypsum increases, or increase as the amount of gypsum decreases; otherwise, the two reaction systems will inhibit each other, hindering strength growth. Furthermore, the ratio of fly ash, quicklime, and cement clinker should be maintained within a certain range. Quicklime, in particular, has excellent hydration reaction capabilities, effectively improving the early and mid-stage strength of the material. However, excessive quicklime will cause the water to boil, leading to excessively high temperatures in the reaction system, destroying the formation of the crystalline structure, and causing the material to become loose.

[0116] Referring to Tables 7 and 8, it can be seen that the addition and proportion of activators have a significant impact on the strength of the filler. Controlling the total amount of active activator within 0.5% to 2% generally achieves a good activating effect, thus improving the filler strength. However, adding too much sodium hydroxide and sodium salts can lead to efflorescence. Therefore, the amount of sodium sulfate should decrease as the amount of sodium hydroxide increases, or increase as the amount of sodium hydroxide decreases. Furthermore, the amount of sodium hydroxide should be as small as possible compared to the amount of water glass, ensuring that the activation process of the cementitious material is primarily driven by water glass, with sodium hydroxide playing a secondary role. In necessary cases, sodium hydroxide can be added less or not at all, especially when the amount of sodium sulfate added is high. This will help avoid efflorescence.

[0117] In summary, this application provides a multi-source solid waste composite backfill cementitious material, its preparation method, and a backfill material containing the material. The multi-source solid waste composite backfill cementitious material provided in this application comprises: 15.5-20.5 parts gypsum powder, 10-15 parts sodium sulfate, 22.5-27.5 parts water slag powder, 22.5-27.5 parts fly ash, 2.5-7.5 parts cement clinker, 7.5-12.5 parts quicklime, and 0.5-2 parts activation agent. It can be mixed with gold mine tailings or tailings of other fineness to prepare backfill material. In the preparation method of the multi-source solid waste composite backfill cementitious material provided in this application, the mechanical activation time of the water slag is 30-50 min. The backfill material provided in this application has a spread of 20-50 cm and a later strength of 2.3-2.5 MPa, and can be used for backfilling in mining.

[0118] This application utilizes sodium sulfate to modify gypsum extracted from a bio-oxidation solution, followed by drying and grinding to obtain gypsum powder. The gypsum powder and mechanically activated water slag powder constitute a sulfate reaction system. In this system, gypsum provides a portion of SO4 for the formation of hydration products. 2- In addition to a suitable alkaline environment, another part of the reaction requires SO4. 2-Provided by sodium sulfate, gypsum and sodium sulfate simultaneously activate the slag in the reaction, generating calcium sulfoaluminate and ettringite crystals. This method effectively improves the water retention performance of cementitious materials and promotes the early and mid-term strength enhancement of filling materials and the generation of early and mid-term hydration products. In addition, this application also introduces fly ash, quicklime, cement clinker and active activator to form an alkaline reaction system, which accelerates the hydration rate of materials and increases the amount of hydration products in the later stage, generating hydrated calcium aluminosilicate gel, hydrated calcium silicate and other hydration products. The ettringite generated in the early stage of setting and the hydrated calcium aluminosilicate gel generated in the later stage continuously crystallize, promoting the continuous progress of the reaction. At the same time, through the close interweaving of the two in the material, the setting strength of the material in the later stage is greatly improved.

[0119] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A method for preparing a multi-source solid waste composite filling cementitious material, characterized in that, The multi-source solid waste composite filling cementitious material comprises the following raw materials in parts by weight: 15.5-20.5 parts gypsum, 10-15 parts sodium sulfate, 22.5-27.5 parts water slag powder, 22.5-27.5 parts fly ash, 2.5-7.5 parts cement clinker, 7.5-12.5 parts quicklime, and 0.5-2 parts activity activator; The gypsum mentioned is gypsum extracted from biological oxidation liquid; Includes the following steps: S1. Water slag and water are mixed at a mass ratio of (0.8-1.2):1 to form a slurry, which is then poured into a ball mill for mechanical activation. The mixture is dried in an oven, then ground and sieved to obtain water slag micro powder. The activity coefficient of the water slag micro powder is ≥0.25, and the specific surface area is ≥600 m². 2 / kg; S2, prepare a sodium sulfate solution with a concentration of 30%-80%, and spray the sodium sulfate solution evenly onto the gypsum surface without dead angles according to the expected weight parts through a spraying device. After drying in an oven, grind to obtain gypsum powder with a fineness greater than 200 mesh. S3, Sodium hydroxide and water glass are mixed evenly in a mass ratio of (0-3):4 to obtain an active activator; S4. The gypsum powder, the water slag powder, the active activator, fly ash, cement clinker and quicklime are mixed and stirred evenly according to the expected weight parts to obtain the multi-source solid waste composite filling cementitious material.

2. The preparation method of the multi-source solid waste composite filling cementitious material according to claim 1, characterized in that, In step S1, the mechanical activation time is 30-50 minutes, the sieving is performed by vibrating sieving to sieve the water slag through a 200-mesh screen, and the drying oven is set to 100-105℃ for 24-28 hours.

3. The preparation method of the multi-source solid waste composite filling cementitious material according to claim 2, characterized in that, In step S3, the water glass is industrial powder sodium silicate with an effective content greater than 95% and a modulus of 1.5; the sodium hydroxide is industrial powder sodium hydroxide with an effective content greater than 90%.

4. The preparation method of the multi-source solid waste composite filling cementitious material according to claim 3, characterized in that, In step S2, the oven is set to 100-105℃ for 12-16 hours, and the sodium sulfate solution is prepared using industrial powder sodium sulfate with an effective content of more than 90%.

5. The preparation method of the multi-source solid waste composite filling cementitious material according to claim 4, characterized in that, In step S4, the cement clinker is silicate cement clinker, and the total mass percentage of CaO, SiO2, Al2O3 and Fe2O3 in the silicate cement clinker is greater than 95%; the quicklime is calcareous quicklime with a CaO mass percentage of more than 60%.

6. A filling material, characterized in that, It includes multi-source solid waste composite backfill cementitious material and tailings prepared by the preparation method according to any one of claims 1-5.

7. The filling material according to claim 6, characterized in that, The tailings are gold mine tailings.

8. The filling material according to claim 7, characterized in that, The tailings are tailings with a fineness of 100-400 mesh.

9. The filling material according to claim 6, characterized in that, The filler has a spread of 20-50 cm and a 28-day strength of 2.3-2.5 MPa.

Citation Information

Patent Citations

  • Clinker-free fly ash composite cementing material, preparation method thereof and coal mine filling paste

    CN114213046A

  • Superfine tailing filling cementing material mainly prepared from copper slag and fly ash and filling material of superfine tailing filling cementing material

    CN116496009A